Investigating Significant Issues of BIM Implementation in Industrialised Building System Design and Production Process - Tsai, Kai Len; Soon Ern, Peniel Ang (International Journal of Sustainable Construction Engineering and Technology, 2021)
Industrialised Building System (IBS) has been considered a construction method to accelerate the development of the construction industry in attempt to boost the economic growth of Malaysia. With the slow uptake of IBS method in Malaysian construction industry, Building Information Modelling (BIM) technology was introduced as a IBS catalyst to improve IBS process in term of its productivity and efficacy. However, the advantages of BIM implementation are not fully acquired in IBS industry. Therefore, there is a need to investigate the issues encountered when BIM implemented in IBS design and IBS production process in Malaysia. The preliminary study adopted both literature review and semi-structured interview as research technique. Four semi-structured interview were conducted with the industry experts who have more than 5 years of experience in both IBS and BIM fields to gain insight into the issues of BIM implementation in both IBS design and production process. The likert scale of agreed level was indicated by the respondents simultaneously while investigating the issues of BIM implementation in IBS design and production process during the interview. The interview data was collected and analysed by measuring mean agreed level to issues of BIM implementation in IBS design and production process and identifying the most significant issues of BIM implementation in IBS process across responses from interview using excel tool and content analysis. The results showed that the most significant issues are encountered when BIM is implemented in IBS design process rather than in IBS production process. The most significant issue is the lack of early collaboration among IBS players in the beginning of IBS design stage in a BIM project. In addition, the lack of knowledge and understanding on IBS design and installation among the project stakeholder, especially consultants in the BIM integrated projects leads to the increase of IBS design time, and causes the late confirmation of informed decision of the IBS component design. It can further affect the productivity of IBS production process. Therefore, the issues of BIM implementation in IBS design process should be tackled early to improve the BIM implementation in IBS industry in Malaysia.